Peningkatan Hasil Belajar Siswa pada Pembelajaran Matematika Menggunakan Model Problem Based Learning di Kelas V Fase C SD Negeri 28 Air Tawar Timur - Novita, Novita; Mansurdin, Mansurdin (Lembaga Yasin AlSys, 2025)
This classroom action research aimed to improve students' learning outcomes in mathematics by implementing the Problem Based Learning (PBL) model in fifth-grade students at SD Negeri 28 Air Tawar Timur, Padang, Indonesia. The study addressed low mathematics performance due to teacher-centered instruction by applying a contextual and collaborative approach. The method used was classroom action research conducted in two cycles. Data were collected through tests, observations, and documentation. The results showed that the application of the PBL model improved students' engagement and performance. The average knowledge score increased from 82.65 in cycle I to 84.85 in cycle II, and the skill aspect rose from 75.5 to 84.5. Affective aspects also improved, particularly in collaboration, critical thinking, and independence. The study concludes that the PBL model is effective in enhancing mathematics learning outcomes for fifth-grade students.